In Search of Forfeited Fiduciary Assurance: A Justice Approach - Novi Rizka Permatasari; Hartiwiningsih Hartiwiningsih; Pujiyono Suwadi (Faculty of Law, University of Muhammadiyah Malang, 2025)
This study examines the legal consequences and proposes a fair model of confiscation that balances the interests of creditors, debtors, and the state. The research employs a normative legal approach, integrating John Rawls’ theory of justice and progressive legal theory, and applies descriptive methods and deductive syllogistic analysis to examine relevant doctrines, legal principles, and judicial practices. The findings reveal significant gaps in current fiduciary regulations, particularly the absence of mechanisms to address the consequences of state confiscation, to provide compensation to affected parties, and to protect receivables rights in cases of loss or damage. In response, the study proposes a reconstructed legal framework that introduces a sanctioning scheme coupled with proportional compensation, explicitly incorporated into court judgments. This model upholds procedural justice and equality among parties, aligning with Rawls’ difference principle. The study concludes that revising fiduciary regulations to include explicit provisions for state confiscation and associated compensation mechanisms should enhance legal certainty, ensure proportional protection of all parties, and promote a fair and effective enforcement system.